Low-density thermal insulation foam concrete and preparation method thereof

By using waste feather fibers and bio-based polyurethane solutions in foam concrete to form a stable network support structure, and combining the porous structures of shrimp shell chitin fibers and mesoporous silica powder, the shortcomings of traditional foam concrete in terms of insulation and strength are solved, and efficient insulation performance and strength improvement are achieved.

CN119638485APending Publication Date: 2025-03-18WUXUE JINGCHENG CONSTR ENG CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411886741.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional foam concrete has shortcomings in thermal insulation and strength, resulting in limited application in building structures and long-term use will lead to performance degradation.

Method used

A low-density thermally insulated foam concrete is used to prepare a low-density thermally insulated foam concrete. By dispersing waste feather fibers in a bio-based polyurethane solution, and adding cement, fly ash, foaming agent, shrimp shell chitin fibers and mesoporous silica powder, a stable network support structure and porous structure are formed by stirring, standing, ultrasound and other steps.

Benefits of technology

It significantly improves the insulation performance and strength of foam concrete, while achieving the requirements of low density, ensuring the stability and integrity of the material, and is suitable for widespread use in building structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638485A_ABST
    Figure CN119638485A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses low-density thermal insulation foam concrete and a preparation method thereof. The preparation method of the low-density thermal-insulation foam concrete comprises the following steps: dispersing waste feather fibers in a bio-based polyurethane solution, stirring, standing, carrying out ultrasonic treatment, adding cement, fly ash, a foaming agent, water and Tween-80, stirring, and standing to obtain a pretreated concrete blank; the preparation method comprises the following steps: dispersing mesoporous silica powder and lauryl sodium sulfate in water, stirring, performing ultrasonic treatment, adding shrimp shell chitin fibers, stirring, filtering, collecting solids, and drying to obtain a modified shrimp shell chitin fiber compound; mixing the pretreated concrete blank and the modified shrimp shell chitin fiber compound, stirring, performing ultrasonic treatment, pouring into a mold, and curing to obtain the low-density thermal insulation foam concrete. The low-density foam concrete disclosed by the invention is good in thermal insulation performance, high in strength, simple in preparation method and suitable for large-scale popularization and production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a low-density thermal insulation foam concrete and a preparation method thereof. Background Art

[0002] In the field of modern construction, the performance of materials plays a vital role in the overall quality, energy efficiency and functional realization of buildings. As an emerging building material, foamed concrete has been widely used in many construction projects. However, with the development of construction technology and the continuous improvement of building performance requirements, traditional foamed concrete has gradually exposed some problems, especially in terms of thermal insulation and strength, two key properties.

[0003] In terms of thermal insulation performance, building energy conservation has become an important development trend in the global construction industry. Although traditional foam concrete has a certain thermal insulation capacity, its pore distribution and size are not uniform, and there are many connected pores, which create conditions for heat conduction and convection. During the heat conduction process, heat can be transferred through the gas in the pores and the pore wall materials, and the connected pores intensify the gas convection, thereby reducing the thermal insulation effect. In terms of the properties of the material itself, the thermal conductivity of the raw materials used in traditional foam concrete and its hydration products is relatively high, and it cannot effectively block the transfer of heat. This poor thermal insulation performance will cause the building to consume more energy to maintain the indoor temperature during use, increase energy costs, and is not conducive to the realization of energy conservation and emission reduction goals.

[0004] In terms of strength, due to its special porous structure, traditional foam concrete contains a large number of bubbles, which to a certain extent destroy the continuity and integrity of the material. When subjected to external loads, the stress is unevenly distributed inside the material, and stress concentration is likely to occur around the bubbles. At the same time, the interfacial bonding strength between the bubbles and the cement matrix is ​​often low. When subjected to pressure, cracks are prone to appear at the interface and expand rapidly, eventually leading to the destruction of the material. This lower strength characteristic greatly limits the application of traditional foam concrete in building structures that need to bear heavy weights or are frequently subjected to external forces. For example, in scenarios such as the load-bearing structures of high-rise buildings and the supporting parts of bridges, it cannot meet the requirements of structural safety and stability.

[0005] CN 117003584 A discloses a lightweight thermal insulation composite foam concrete, which utilizes the microporous structure of bamboo fiber to absorb the modified liquid. The modified bamboo fiber has good compatibility with the foaming agent, and can easily pass through the foam without destroying the foam when the concrete mixture is stirred, so that after the concrete is solidified, the bamboo fiber penetrates the pores inside the concrete in large quantities, making up for the strength loss caused by the decrease in density at the pores, and improving the strength. At the same time, the coarse aggregate and fine aggregate are compounded to make the foam concrete stronger and more fluid, further improving the lightweight and strength performance of the foam concrete. However, this method also has certain limitations, that is, the bamboo fiber is in an alkaline cement environment for a long time, and degradation or chemical changes will occur, resulting in the destruction of its structure, thereby reducing the reinforcing effect on the concrete pores, causing the strength to decrease over time, and the porosity will also increase due to structural damage, which will have an adverse effect on the thermal insulation performance. In addition, although the compounding of coarse aggregate and fine aggregate improves some properties, the interface bonding between aggregate and cement matrix is ​​always a difficult problem. If the interface is not tightly bonded enough, the interface will easily become a weak link when subjected to external force, causing cracks to expand, reducing the strength of the concrete, destroying the integrity of the foam structure, and affecting the thermal insulation performance.

[0006] CN 109020383 A discloses a high-strength foamed concrete, which utilizes reinforcing fibers, calcium carbonate whiskers and carbon nanotubes to be randomly distributed and overlapped inside the concrete, thereby reducing the surface tension of the foam, playing a reinforcing role, supporting aggregates to prevent sinking and segregation, reducing microcracks caused by cement matrix shrinkage and delaying their expansion, and achieving a toughening effect. At the same time, glass powder, montmorillonite, metakaolin, etc. are added to optimize the pore size distribution, making the concrete denser and stronger. Although this method effectively improves the strength of foamed concrete so that it can meet the strength requirements of building structures, it has certain limitations in terms of thermal insulation performance. Specifically, reinforcing fibers, calcium carbonate whiskers and carbon nanotubes themselves have certain thermal conductivity, and the network structure formed by their overlap in concrete increases the heat conduction path. Heat can be transferred faster through these fibers and whiskers, thereby reducing the thermal insulation performance of foamed concrete and making it easier to dissipate heat. In addition, if the heat generated by the secondary hydration reaction between glass powder and calcium hydroxide in cement paste cannot be dissipated in time, it may cause the temperature inside the concrete to rise and generate a temperature gradient. This temperature gradient will cause heat to transfer faster from the high-temperature area to the low-temperature area, destroy the uniformity of the thermal insulation performance, increase the rate of heat loss, and especially in a low-temperature environment, reduce the thermal insulation effect of the foam concrete.

[0007] In summary, in the context of increasingly stringent requirements for material performance in modern buildings, the shortcomings of traditional foam concrete in terms of thermal insulation and strength have become a key factor restricting its further development and widespread application. Therefore, how to develop a new type of foam concrete that can simultaneously improve thermal insulation performance, enhance strength and effectively control density has become a technical problem that needs to be solved in this field, which is of great significance for promoting the sustainable development of the construction industry and improving the quality of buildings. Summary of the invention

[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing low-density thermal insulation foam concrete.

[0009] A method for preparing low-density thermal insulation foam concrete comprises the following steps:

[0010] S1. Dispersing waste feather fibers in a bio-based polyurethane solution, stirring, standing, ultrasonicating, adding cement, fly ash, foaming agent, water, Tween-80, stirring, standing, to obtain a pretreated concrete body;

[0011] S2, dispersing mesoporous silica powder and sodium dodecyl sulfate in water, stirring, ultrasonicating, adding shrimp shell chitin fiber, stirring, filtering, collecting solids, and drying to obtain a modified shrimp shell chitin fiber composite;

[0012] S3, mixing the pretreated concrete body and the modified shrimp shell chitin fiber composite, stirring, ultrasonicating, pouring into a mold, and curing to obtain a low-density thermal insulation foam concrete.

[0013] Preferably, the weight ratio of waste feather fiber, bio-based polyurethane solution, cement, fly ash, foaming agent, water, Tween-80, mesoporous silica powder, sodium dodecyl sulfate and shrimp shell chitin fiber is 5-8:16-20:25-35:8-10:0.5-1:13.85-18.76:0.15-0.24:1-3:0.3-0.7:2-6.

[0014] Preferably, in the method for preparing the bio-based polyurethane solution, castor oil-based polyol is dissolved in anhydrous ethanol, dibutyltin dilaurate is added, diisocyanate is added, the diisocyanate is added at a rate of 5-10% per minute based on the total weight of the diisocyanate, stirred at 60-65° C. for 2-3 hours at a stirring rate of 300-400 r / min, and cooled to obtain a bio-based polyurethane solution.

[0015] Preferably, the weight ratio of castor oil-based polyol, anhydrous ethanol, dibutyltin dilaurate and diisocyanate is 5-10:10-15:0.05-0.1:2-6.

[0016] Preferably, in step S1, the waste feather fibers are dispersed in the bio-based polyurethane solution and then stirred, the stirring time is 1-2 hours, and the stirring speed is 300-500 r / min.

[0017] Preferably, in step S1, the standing temperature is 45-50° C. and the standing time is 2-3 h.

[0018] Preferably, in step S1, the ultrasonic treatment time is 0.2-0.6 h, and the ultrasonic frequency is 40-50 kHz.

[0019] Preferably, in step S1, cement, fly ash, foaming agent, water and Tween-80 are added and stirred at a temperature of 50-55° C., a stirring time of 1-2 h and a stirring speed of 600-800 r / min.

[0020] Preferably, in step S1, cement, fly ash, foaming agent, water and Tween-80 are added, stirred and then allowed to stand for 0.5-1 h.

[0021] Preferably, in step S2, the mesoporous silica powder and sodium dodecyl sulfate are dispersed in water and then stirred. The stirring time is 0.5-1 h and the stirring speed is 300-400 r / min.

[0022] Preferably, in step S2, the ultrasonic treatment time is 0.2-0.4 h, and the ultrasonic frequency is 50-60 kHz.

[0023] Preferably, in step S2, chitin fibers from shrimp shells are added at a rate of 10-15% per minute based on the total weight of the chitin fibers from shrimp shells.

[0024] Preferably, in step S2, the shrimp shell chitin fibers are added and stirred for 1-2 hours at a speed of 300-400 r / min.

[0025] Preferably, in step S2, the drying temperature is 50-55°C and the drying time is 24-30h.

[0026] Preferably, in step S3, the stirring time is 0.5-1h, and the stirring speed is 600-700r / min.

[0027] Preferably, in step S3, the ultrasonic time is 0.1-0.3 h, and the ultrasonic frequency is 50-60 kHz.

[0028] Preferably, in step S3, the curing time is 19-23 days, the curing temperature is 18-22° C., and the curing relative humidity is 85-95%.

[0029] A low-density thermal insulation foam concrete is prepared by adopting the preparation method of the low-density thermal insulation foam concrete.

[0030] Beneficial effects:

[0031] In the present invention, the isocyanate group in the bio-based polyurethane solution reacts with the active amino group and carboxyl group in the waste feather fiber, so that a stable chemical bond is formed between the feather fiber and the polyurethane, and under the action of Tween-80, the dispersibility of the bio-based polyurethane solution in the system is improved, thereby building a stable network support structure; as the reaction proceeds, the mineral components such as tricalcium silicate and dicalcium silicate in the cement react with water to produce hydration products such as calcium hydroxide and hydrated calcium silicate gel. Among them, the hydrated calcium silicate gel will gradually fill in the feather fiber-polyurethane composite, and the bubbles generated by the foaming agent are evenly distributed therein. At this time, the feather fiber-polyurethane composite, as a reinforcing phase, is intertwined with the cement gel network, and the bubbles are stably confined in the system, forming a preliminary porous structure.

[0032] Mesoporous silica has a low thermal conductivity, and its porous structure can reduce the effective cross-sectional area of ​​heat conduction, increase the tortuosity of the heat conduction path, and effectively prevent heat transfer. In the present invention, the silicon hydroxyl group of mesoporous silica and the hydroxyl group on the shrimp shell chitin fiber undergo hydrogen bonding. At the same time, the porous structure of mesoporous silica interacts with the shrimp shell chitin fiber through physical adsorption, so that the shrimp shell chitin fiber and mesoporous silica are closely combined, and the strength and thermal insulation of the material are enhanced. In addition, the porous structure of mesoporous silica and the network structure formed by the interweaving of shrimp shell chitin fiber and feather fiber cooperate with each other, and under the premise of ensuring a certain strength, the porosity is significantly increased, and the above-mentioned preliminary porous structure effect is cooperated, thereby effectively reducing the density of concrete and achieving the requirement of low density.

[0033] The porous structure of the mesoporous silica of the present invention not only fills the original pores of the system, but also its silanol group reacts chemically with calcium hydroxide in cement gel to generate calcium silicate substances, which enhances the bonding force between materials, further connects various phases, and makes the microstructure present a highly connected three-dimensional network. In this network, bubbles can exist stably, which not only ensures a low-density foam structure, but also makes the structure more stable and complete.

[0034] The pores in the concrete reduce the path of heat conduction, and the foam structure further reduces the thermal conductivity. The two work synergistically to significantly improve the thermal insulation performance. The foam concrete prepared by the present invention has the characteristics of low density, high strength and good thermal insulation, and the preparation method is simple, which is suitable for large-scale promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1This is a comparison chart of thermal conductivity tests of foamed concrete prepared in Example 5 and Comparative Examples 1-2.

[0036] Figure 2 This is a comparison chart of dry apparent density tests of foamed concrete prepared in Example 5 and Comparative Examples 1-2.

[0037] Figure 3 The figure is a comparison chart of the compressive strength test of the foamed concrete prepared in Example 5 and Comparative Examples 1-2.

[0038] Figure 4 The softening coefficient test comparison chart of the foamed concrete prepared in Example 5 and Comparative Examples 1-2 is shown. DETAILED DESCRIPTION

[0039] The waste feather fibers used below are obtained by processing in step 2.2.2 Pretreatment of Feather Fibers in reference [Qian Wenzhen. Functional Recycling of Waste Biomass Hair Fibers [D]. Northwest Normal University, 2017.].

[0040] The cement used below was purchased from a local cement plant and is PO42 ordinary Portland cement; the Tween-80 used below was purchased from Sinopharm Chemical Reagent Co., Ltd., model T80; the mesoporous silica powder used below was purchased from Wuhu Xinda New Material Technology Co., Ltd., model XD-S05JK; the shrimp shell chitin fiber used below was purchased from Shaanxi Jingfei Biotechnology Co., Ltd.; the tea saponin cement foaming agent used below was purchased from Yifeng County Chazhiyuan Technology Co., Ltd.; the castor oil-based polyol used below was purchased from Shanghai Huanyang Chemical Technology Co., Ltd.

[0041] The present invention will be further explained below in conjunction with specific embodiments.

[0042] Example 1

[0043] A method for preparing low-density thermal insulation foam concrete comprises the following steps:

[0044] S1. Disperse 50g of waste feather fiber in 160g of bio-based polyurethane solution, stir for 1h at a stirring speed of 300r / min, stand at 45°C for 2h, perform ultrasonic treatment for 0.2h at an ultrasonic frequency of 40kHz, add 250g of cement, 80g of fly ash, 5g of tea saponin cement foaming agent, 138.5g of water, and 1.5g of Tween-80, stir at 50°C for 1h at a stirring speed of 600r / min, stand for 0.5h, and obtain a pretreated concrete body;

[0045] S2, 10g of mesoporous silica powder and 3g of sodium dodecyl sulfate were dispersed in 400g of water, stirred for 0.5h at a stirring speed of 300r / min, ultrasonically treated for 0.2h at an ultrasonic frequency of 50kHz, 20g of shrimp shell chitin fiber was added, and the total weight of the shrimp shell chitin fiber was used as a basis, and the shrimp shell chitin fiber was added at a speed of 10% per minute, stirred for 1h at a stirring speed of 300r / min, filtered, the solid was collected, and dried at 50°C for 24h to obtain a modified shrimp shell chitin fiber composite;

[0046] S3. Mix the pretreated concrete body and the modified shrimp shell chitin fiber composite, stir for 0.5 h, the stirring speed is 600 r / min, ultrasonic for 0.1 h, the ultrasonic frequency is 50 kHz, pour into a mold, and cure for 19 days at a curing temperature of 18° C. and a curing relative humidity of 85% to obtain a low-density thermal insulation foam concrete.

[0047] The preparation method of the bio-based polyurethane solution is as follows: 50 g of castor oil-based polyol is dissolved in 100 g of anhydrous ethanol, 0.5 g of dibutyltin dilaurate is added, 20 g of dicyclohexylmethane diisocyanate is added, and the total weight of dicyclohexylmethane diisocyanate is used as the basis, and the dicyclohexylmethane diisocyanate is added at a rate of 5% per minute. The mixture is stirred at 60° C. for 2 h at a stirring rate of 300 r / min, and cooled to obtain a bio-based polyurethane solution.

[0048] Example 2

[0049] A method for preparing low-density thermal insulation foam concrete comprises the following steps:

[0050] S1. Disperse 80g of waste feather fiber in 200g of bio-based polyurethane solution, stir for 2h at a stirring speed of 500r / min, stand at 50°C for 3h, ultrasonically treat for 0.6h at an ultrasonic frequency of 50kHz, add 350g of cement, 100g of fly ash, 10g of tea saponin cement foaming agent, 187.6g of water, and 2.4g of Tween-80, stir at 55°C for 2h at a stirring speed of 800r / min, and stand for 1h to obtain a pretreated concrete body;

[0051] S2, dispersing 30g of mesoporous silica powder and 7g of sodium dodecyl sulfate in 500g of water, stirring for 1h, stirring at a speed of 400r / min, ultrasonic treatment for 0.4h, ultrasonic frequency of 60kHz, adding 60g of shrimp shell chitin fiber, based on the total weight of the shrimp shell chitin fiber, the shrimp shell chitin fiber addition rate is 15% per minute, stirring for 2h, stirring at a speed of 400r / min, filtering, collecting solids, and drying at 55°C for 30h to obtain a modified shrimp shell chitin fiber composite;

[0052] S3. The pretreated concrete body and the modified shrimp shell chitin fiber composite were mixed, stirred for 1 hour at a stirring speed of 700 r / min, ultrasonicated for 0.3 hour at an ultrasonic frequency of 60 kHz, poured into a mold, and cured for 23 days at a curing temperature of 22° C. and a curing relative humidity of 95% to obtain a low-density thermal insulation foam concrete.

[0053] The preparation method of the bio-based polyurethane solution is as follows: 100g of castor oil-based polyol is dissolved in 150g of anhydrous ethanol, 1g of dibutyltin dilaurate is added, 60g of dicyclohexylmethane diisocyanate is added, and the total weight of dicyclohexylmethane diisocyanate is used as the basis, and the dicyclohexylmethane diisocyanate is added at a rate of 10% per minute. The mixture is stirred at 65°C for 3h at a stirring rate of 400r / min, and cooled to obtain a bio-based polyurethane solution.

[0054] Example 3

[0055] A method for preparing low-density thermal insulation foam concrete comprises the following steps:

[0056] S1. Disperse 60g of waste feather fiber in 170g of bio-based polyurethane solution, stir for 1.2h at a stirring speed of 350r / min, stand at 46°C for 2.2h, perform ultrasonic treatment for 0.3h at an ultrasonic frequency of 42kHz, add 270g of cement, 85g of fly ash, 6g of tea saponin cement foaming agent, 150.336g of water, and 1.664g of Tween-80, stir at 51°C for 1.2h at a stirring speed of 650r / min, stand for 0.6h, and obtain a pretreated concrete body;

[0057] S2, 15g of mesoporous silica powder and 4g of sodium dodecyl sulfate were dispersed in 420g of water, stirred for 0.6h at a stirring speed of 320r / min, ultrasonically treated for 0.25h at an ultrasonic frequency of 52kHz, 30g of shrimp shell chitin fiber was added, and the shrimp shell chitin fiber was added at a speed of 11% per minute based on the total weight of the shrimp shell chitin fiber, stirred for 1.2h at a stirring speed of 320r / min, filtered, the solid was collected, and dried at 51°C for 26h to obtain a modified shrimp shell chitin fiber composite;

[0058] S3. The pretreated concrete body and the modified shrimp shell chitin fiber composite were mixed, stirred for 0.6 h, the stirring speed was 620 r / min, ultrasonic was applied for 0.15 h, the ultrasonic frequency was 52 kHz, poured into a mold, and cured for 20 days at a curing temperature of 19° C. and a curing relative humidity of 87% to obtain a low-density thermal insulation foam concrete.

[0059] Preparation method of bio-based polyurethane solution: dissolve 60g of castor oil-based polyol in 110g of anhydrous ethanol, add 0.6g of dibutyltin dilaurate, add 30g of isophorone diisocyanate, based on the total weight of isophorone diisocyanate, add isophorone diisocyanate at a rate of 6% per minute, stir at 61°C for 2.2h, stir at a rate of 320r / min, cool, and obtain a bio-based polyurethane solution.

[0060] Example 4

[0061] A method for preparing low-density thermal insulation foam concrete comprises the following steps:

[0062] S1. Disperse 70g of waste feather fiber in 190g of bio-based polyurethane solution, stir for 1.8h at a stirring speed of 450r / min, stand at 49°C for 2.8h, perform ultrasonic treatment for 0.5h at an ultrasonic frequency of 48kHz, add 330g of cement, 95g of fly ash, 9g of tea saponin cement foaming agent, 175.796g of water, and 2.204g of Tween-80, stir at 54°C for 1.8h at a stirring speed of 750r / min, stand for 0.9h, and obtain a pretreated concrete body;

[0063] S2, 25g of mesoporous silica powder and 6g of sodium dodecyl sulfate were dispersed in 480g of water, stirred for 0.9h, the stirring speed was 380r / min, ultrasonic treatment was performed for 0.35h, the ultrasonic frequency was 58kHz, 50g of shrimp shell chitin fiber was added, based on the total weight of the shrimp shell chitin fiber, the shrimp shell chitin fiber was added at a rate of 14% per minute, stirred for 1.8h, the stirring speed was 380r / min, filtered, the solid was collected, and dried at 54°C for 28h to obtain a modified shrimp shell chitin fiber composite;

[0064] S3. Mix the pretreated concrete body and the modified shrimp shell chitin fiber composite, stir for 0.9 h, the stirring speed is 680 r / min, ultrasonic for 0.25 h, the ultrasonic frequency is 58 kHz, pour into a mold, and cure for 22 days at a curing temperature of 21° C. and a curing relative humidity of 93% to obtain a low-density thermal insulation foam concrete.

[0065] Preparation method of bio-based polyurethane solution: dissolve 90g of castor oil-based polyol in 140g of anhydrous ethanol, add 0.9g of dibutyltin dilaurate, add 50g of isophorone diisocyanate, based on the total weight of isophorone diisocyanate, the isophorone diisocyanate addition rate is 9% per minute, stir at 64°C for 2.8h, the stirring speed is 380r / min, cool, and obtain a bio-based polyurethane solution.

[0066] Example 5

[0067] A method for preparing low-density thermal insulation foam concrete comprises the following steps:

[0068] S1. Disperse 65g of waste feather fiber in 180g of bio-based polyurethane solution, stir for 1.5h at a stirring speed of 400r / min, stand at 47°C for 2.5h, ultrasonically treat for 0.4h at an ultrasonic frequency of 45kHz, add 300g of cement, 90g of fly ash, 7g of tea saponin cement foaming agent, 163.075g of water, and 1.925g of Tween-80, stir at 52°C for 1.5h at a stirring speed of 700r / min, and stand for 0.7h to obtain a pretreated concrete body;

[0069] S2, 20g of mesoporous silica powder and 5g of sodium dodecyl sulfate were dispersed in 450g of water, stirred for 0.7h at a stirring speed of 350r / min, ultrasonically treated for 0.3h at an ultrasonic frequency of 55kHz, 40g of shrimp shell chitin fiber was added, and the shrimp shell chitin fiber was added at a speed of 12% per minute based on the total weight of the shrimp shell chitin fiber, stirred for 1.5h at a stirring speed of 350r / min, filtered, the solid was collected, and dried at 52°C for 27h to obtain a modified shrimp shell chitin fiber composite;

[0070] S3. Mix the pretreated concrete body and the modified shrimp shell chitin fiber composite, stir for 0.7h, the stirring speed is 650r / min, ultrasonic for 0.2h, the ultrasonic frequency is 55kHz, pour into a mold, and cure for 21 days at a curing temperature of 20°C and a curing relative humidity of 90% to obtain a low-density thermal insulation foam concrete.

[0071] Preparation method of bio-based polyurethane solution: dissolve 70g castor oil-based polyol in 120g anhydrous ethanol, add 0.7g dibutyltin dilaurate, add 40g diphenylmethane diisocyanate, based on the total weight of diphenylmethane diisocyanate, the diphenylmethane diisocyanate addition rate is 7% per minute, stir at 62°C for 2.5h, the stirring speed is 350r / min, cool, and obtain a bio-based polyurethane solution.

[0072] Comparative Example 1

[0073] A method for preparing foamed concrete, characterized in that it comprises the following steps:

[0074] S1, 20g of mesoporous silica powder and 5g of sodium dodecyl sulfate were dispersed in 450g of water, stirred for 0.7h at a stirring speed of 350r / min, ultrasonically treated for 0.3h at an ultrasonic frequency of 55kHz, 40g of shrimp shell chitin fiber was added, and the shrimp shell chitin fiber was added at a speed of 12% per minute based on the total weight of the shrimp shell chitin fiber, stirred for 1.5h at a stirring speed of 350r / min, filtered, the solid was collected, and dried at 52°C for 27h to obtain a modified shrimp shell chitin fiber composite;

[0075] S2. Mix 65g of waste feather fiber, 180g of bio-based polyurethane solution, 300g of cement, 90g of fly ash, 7g of tea saponin cement foaming agent, 163.075g of water, 1.925g of Tween-80, and a modified shrimp shell chitin fiber composite, stir for 0.7h at a stirring speed of 650r / min, perform ultrasound for 0.2h, and perform ultrasound at a frequency of 55kHz. Pour the mixture into a mold, and cure for 21 days at a curing temperature of 20°C and a curing relative humidity of 90% to obtain foamed concrete.

[0076] Preparation method of bio-based polyurethane solution: dissolve 70g castor oil-based polyol in 120g anhydrous ethanol, add 0.7g dibutyltin dilaurate, add 40g diphenylmethane diisocyanate, based on the total weight of diphenylmethane diisocyanate, the diphenylmethane diisocyanate addition rate is 7% per minute, stir at 62°C for 2.5h, the stirring speed is 350r / min, cool, and obtain a bio-based polyurethane solution.

[0077] Comparative Example 2

[0078] A method for preparing foamed concrete comprises the following steps:

[0079] S1. Disperse 65g of waste feather fiber in 180g of bio-based polyurethane solution, stir for 1.5h at a stirring speed of 400r / min, stand at 47°C for 2.5h, ultrasonically treat for 0.4h at an ultrasonic frequency of 45kHz, add 300g of cement, 90g of fly ash, 7g of tea saponin cement foaming agent, 163.075g of water, and 1.925g of Tween-80, stir at 52°C for 1.5h at a stirring speed of 700r / min, and stand for 0.7h to obtain a pretreated concrete body;

[0080] S2. Mix the pretreated concrete body, 20 g of mesoporous silica powder, and 40 g of shrimp shell chitin fiber, stir for 0.7 h, the stirring speed is 650 r / min, ultrasonic for 0.2 h, the ultrasonic frequency is 55 kHz, pour into a mold, and cure for 21 days at a curing temperature of 20° C. and a curing relative humidity of 90% to obtain foamed concrete.

[0081] Preparation method of bio-based polyurethane solution: dissolve 70g castor oil-based polyol in 120g anhydrous ethanol, add 0.7g dibutyltin dilaurate, add 40g diphenylmethane diisocyanate, based on the total weight of diphenylmethane diisocyanate, the diphenylmethane diisocyanate addition rate is 7% per minute, stir at 62°C for 2.5h, the stirring speed is 350r / min, cool, and obtain a bio-based polyurethane solution.

[0082] Test Example 1

[0083] The thermal conductivity of the foamed concrete prepared in Example 5 and Comparative Examples 1-2 was tested as follows:

[0084] The foamed concrete prepared in Example 5 and Comparative Examples 1-2 were made into rectangular specimens of the same size, ensuring that the surface of the specimens was flat and the thickness was uniform; the specimens were placed in a blast drying oven and dried to constant weight; the intelligent thermal conductivity tester (DRCD-3030) was turned on and preheated for 30 minutes; the specimens were placed in the test position of the tester, ensuring that the specimens were in close contact with the hot plate and the cold plate; the parameters were set and the measurement was started; when the test reached the set conditions or a stable state, the test was stopped and the instrument automatically gave the thermal conductivity data, and the above results were recorded as Group 1; the above steps were repeated twice, and the results were recorded as Group 2 and Group 3.

[0085] Test Example 2

[0086] The dry apparent density of the foamed concrete prepared in Example 5 and Comparative Examples 1-2 was tested as follows:

[0087] The foamed concrete prepared in Example 5 and Comparative Examples 1-2 were made into rectangular specimens of the same size, ensuring that the surface of the specimens was flat, the thickness was uniform, and there were no obvious defects; the specimens were placed in a drying oven and dried to constant weight; the electronic balance was leveled and zeroed, the specimens were placed on the balance tray, and the data were recorded. The above results were recorded as Group 1.

[0088] Calculation formula:

[0089] m is the dry mass of the sample;

[0090] V is the sample volume.

[0091] Repeat the above steps twice and record the results as Group 2 and Group 3.

[0092] Depend on Figure 1 , Figure 2It can be seen that the foamed concrete prepared in Example 5 exhibits the best thermal insulation performance, which is due to the fact that the hydrated calcium silicate gel is filled between the feather fiber-polyurethane composite, and the bubbles generated by the foaming agent are evenly distributed therein. The feather fiber-polyurethane composite is intertwined with the cement gel network as a reinforcing phase, and the bubbles are stably confined in the system, forming a preliminary porous structure. While achieving the requirement of low density, the pores in the concrete reduce the path of heat conduction, and the foam structure reduces the thermal conductivity. The two work synergistically to improve the thermal insulation performance of the concrete. In addition, the porous structure of mesoporous silica interacts with the shrimp shell chitin fiber through physical adsorption, so that the shrimp shell chitin fiber and the mesoporous silica are closely combined, further enhancing the thermal insulation performance of the material.

[0093] Test Example 3

[0094] The compressive strength and softening coefficient of the foamed concrete prepared in Example 5 and Comparative Examples 1-2 were tested as follows:

[0095] Compressive strength: The foamed concrete prepared in Example 5 and Comparative Examples 1-2 were made into cubic specimens of the same size, ensuring that the surface of the specimens was flat and the thickness was uniform; the specimens were placed in a drying oven and dried to constant weight; the specimens were placed on the lower platen or pad of a pressure testing machine (purchased from Jinan Zhongchuang Industrial Testing System Co., Ltd., model YAW-300), ensuring that the pressure-bearing surface of the specimen was in full contact with the lower platen, and the central axis of the specimen coincided with the central axis of the lower platen; the pressure testing machine was started, and when the upper platen approached the specimen, the ball seat was adjusted to make the contact balanced and the load was applied continuously and evenly; when the specimen was destroyed, the testing machine automatically recorded the destruction load value, and the above results were recorded as Group 1; the above steps were repeated twice, and the results were recorded as Group 2 and Group 3.

[0096] Softening coefficient: The foamed concrete prepared in Example 5 and Comparative Examples 1-2 was made into cube specimens of the same size, ensuring that the surface of the specimen was flat and the thickness was uniform; the specimen was immersed in water, the specimen was taken out of the water, and the excess water on the surface was wiped off; the specimen was placed on the lower plate or pad of the pressure testing machine (purchased from Jinan Zhongchuang Industrial Testing System Co., Ltd., model YAW-300), ensuring that the pressure-bearing surface of the specimen was in full contact with the lower plate, and the central axis of the specimen coincided with the central axis of the lower plate; the pressure testing machine was started, and when the upper plate was close to the specimen, the ball seat was adjusted to make the contact balanced and the load was applied continuously and evenly; when the specimen was destroyed, the testing machine automatically recorded the destruction load value. The above results were recorded as Group 1.

[0097] Calculation formula:

[0098] F f is the compressive strength of the specimen after immersion;

[0099] F0 is the compressive strength of the dry specimen.

[0100] Repeat the above steps twice and record the results as Group 2 and Group 3.

[0101] Depend on Figure 3 , Figure 4 It can be seen that the foamed concrete prepared in Example 5 shows the best strength. This is because the isocyanate group in the bio-based polyurethane solution undergoes a nucleophilic addition reaction with the feather fiber to build a stable network support structure, and the hydroxyl group of the polyurethane interacts with the silanol group in the cement gel through hydrogen bonds, further stabilizing the system structure. At the same time, the porous structure of mesoporous silica interacts with the shrimp shell chitin fiber through physical adsorption, so that the shrimp shell chitin fiber and the mesoporous silica are closely combined, thereby enhancing the strength of the material. In addition, the modified shrimp shell chitin fiber and the feather fiber are intertwined to form a complex interpenetrating network structure, which further enhances the support strength of the system.

[0102] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing low-density thermal insulation foam concrete, characterized in that: The steps include: S1. Dispersing waste feather fibers in a bio-based polyurethane solution, stirring, standing, ultrasonicating, adding cement, fly ash, foaming agent, water, Tween-80, stirring, standing, to obtain a pretreated concrete body; S2, dispersing mesoporous silica powder and sodium dodecyl sulfate in water, stirring, ultrasonicating, adding shrimp shell chitin fiber, stirring, filtering, collecting solids, and drying to obtain a modified shrimp shell chitin fiber composite; S3, mixing the pretreated concrete body and the modified shrimp shell chitin fiber composite, stirring, ultrasonicating, pouring into a mold, and curing.

2. The method for preparing low-density thermal insulation foam concrete according to claim 1, characterized in that: The weight ratio of waste feather fiber, bio-based polyurethane solution, cement, fly ash, foaming agent, water, Tween-80, mesoporous silica powder, sodium dodecyl sulfate and shrimp shell chitin fiber is 5-8:16-20:25-35:8-10:0.5-1:13.85-18.76:0.15-0.24:1-3:0.3-0.7:2-6.

3. The method for preparing low-density thermal insulation foam concrete according to claim 1, characterized in that: In the preparation method of the bio-based polyurethane solution, castor oil-based polyol is dissolved in anhydrous ethanol, dibutyltin dilaurate is added, diisocyanate is added, the diisocyanate is added at a rate of 5-10% per minute based on the total weight of the diisocyanate, stirred at 60-65°C for 2-3h, the stirring speed is 300-400r / min, and cooled to obtain a bio-based polyurethane solution.

4. The method for preparing low-density thermal insulation foam concrete according to claim 3, characterized in that: The weight ratio of castor oil-based polyol, anhydrous ethanol, dibutyltin dilaurate and diisocyanate is 5-10:10-15:0.05-0.1:2-6.

5. The method for preparing low-density thermal insulation foam concrete according to claim 1, characterized in that: In step S1, the waste feather fibers are dispersed in the bio-based polyurethane solution and then stirred. The stirring time is 1-2 hours and the stirring speed is 300-500 r / min.

6. The method for preparing low-density thermal insulation foam concrete according to claim 1, characterized in that: In step S1, the ultrasonic treatment time is 0.2-0.6h, and the ultrasonic frequency is 40-50kHz.

7. The method for preparing low-density thermal insulation foam concrete according to claim 1, characterized in that: In step S2, chitin fibers from shrimp shells are added, and the speed of adding chitin fibers from shrimp shells is 10-15% per minute based on the total weight of the chitin fibers from shrimp shells.

8. The method for preparing low-density thermal insulation foam concrete according to claim 1, characterized in that: In step S2, the drying temperature is 50-55°C and the drying time is 24-30h.

9. The method for preparing low-density thermal insulation foam concrete according to claim 1, characterized in that: In step S3, the curing time is 19-23 days, the curing temperature is 18-22° C., and the curing relative humidity is 85-95%.

10. A low-density thermal insulation foam concrete, characterized in that: The low-density thermal insulation foam concrete is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-strength foam concrete

    CN109020383A

  • Lightweight thermal insulation composite foam concrete

    CN117003584A

  • Calcium silicate micro-nano material library taking cement and 'three wastes' as raw materials and synthesis process

    CN113511834A

  • Ultraviolet curing reaction type wool anti-felting finishing agent, preparation method and finishing process

    CN116752350A

  • Arthrobotrys oligospora chitinase AO-59opt mesoporous silica nano-particles for killing nematodes and preparation method of Arthrobotrys oligospora chitinase AO-59opt mesoporous silica nano-particles

    CN118421612A